Challenges In Diagnosing Systemic Lupus Erythematosus In Children: Clinical And Non-Clinical Factors - Darma, Jason Chrisandy; Hikmah, Zahrah (Syifa'Medika, 2026)
Childhood-onset Systemic Lupus Erythematosus (cSLE) is a separate biological entity with more aggressive immunopathogenesis, faster organ damage accumulation, and greater mortality rates than adult-onset lupus. In tropical, resource-constrained environments such as Indonesia, diagnosis is routinely delayed beyond the clinically critical six-month "window of opportunity," resulting in irreversible damages. The purpose of this literature review is to completely identify the clinical and non-clinical factors of diagnostic delay and to evaluate strategies for overcoming these hurdles. The analysis finds "diagnostic overshadowing" as a main clinical driver, in which symptoms are mistaken for endemic infections like Dengue, Typhoid, and Tuberculosis due to cognitive bias and symptom overlap. Systemically, this is worsened by a "Specialist Void," with regional data indicating less than one pediatric rheumatologist per 26 million children in Southeast Asia, as well as economic constraints where diagnostic testing costs substantially more than empirical antibiotic therapy. These delays are associated with high Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) scores and catastrophic healthcare costs. To break down these barriers, health systems must implement "task-shifting" to provide primary care providers with standardized triage algorithms, use telemedicine networks to bridge geographic isolation, and implement policy reforms to increase access to immunological screening at the secondary healthcare level.